2020
DOI: 10.1101/2020.02.10.941682
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High throughput screening identifies SOX2 as a Super Pioneer Factor that inhibits DNA methylation maintenance at its binding sites

Abstract: 19Access of mammalian transcription factors (TFs) to regulatory regions, an essential 20 event for transcription regulation, is hindered by chromatin compaction involving 21 nucleosome wrapping, repressive histone modifications and DNA methylation. 22TET-dependent active DNA demethylation, SOX2 binding leads to passive 37 demethylation by inhibition of the maintenance methyltransferase DNMT1 during 38 replication. This important finding suggests a novel mechanism allowing TFs to 39 interfere with the epigeneti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 116 publications
(89 reference statements)
2
9
0
Order By: Relevance
“…The expression of the majority of the emTFs exhibited anti-correlation with CpG methylation close to their TFBSs, indicating that these emTFs are likely inducing local DNA demethylation. This is in agreement with previous studies that reported RUNX1 [7,61], RUNX3 [6], SPI1 [6,20,61], BHLHE40 [61], and FOXA1 [22] to induce binding-site directed DNA demethylation.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The expression of the majority of the emTFs exhibited anti-correlation with CpG methylation close to their TFBSs, indicating that these emTFs are likely inducing local DNA demethylation. This is in agreement with previous studies that reported RUNX1 [7,61], RUNX3 [6], SPI1 [6,20,61], BHLHE40 [61], and FOXA1 [22] to induce binding-site directed DNA demethylation.…”
Section: Discussionsupporting
confidence: 94%
“…The strategy relies on the integration of a sequence backbone with known methylation status but containing diverse TF binding motifs followed by bisulfite sequencing of PCR amplicons. The study revealed pioneer TFs that can induce local DNA demethylation and pioneer TFs whose binding have a protective effect against de novo DNA methylation [22]. Using a computational approach, the ELMER (Enhancer Linking by Methylation/Expression Relationships) tool allowed for the large-scale identification of transcriptional enhancers and their target genes based on DNA methylation data (at enhancers) and gene expression [23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence that SOX TFs can act as pioneering factors by directly engaging nucleosomes to regulate chromatin accessibility [45][46][47][48] , which might explain in part the loss of ßcatenin binding in SOX17KO cells. To address this possibility, we performed ATAC-Seq 49 to predict nucleosome occupancy at both classes of enhancers.…”
Section: Sox17 Is Required To Establish a Permissive Chromatin Landscape At A Subset Of Tcfindependent Endodermal Enhancersmentioning
confidence: 99%